CDK1 may promote breast cancer progression through AKT activation and immune modulation - Zeng, Huanhong; Zhuang, Minxue; Liang, Bochuan; Cai, Feili; Lin, Mengbo; Wang, Ruijuan; Wang, Ruo; Zhang, Hui (Frontiers in Oncology, 2025)
BackgroundCyclin-dependent kinase 1 (CDK1) plays a crucial role in regulating the cell cycle, yet its clinical relevance and molecular mechanisms in breast cancer remain insufficiently characterized. This study aimed to comprehensively evaluate CDK1 expression, prognostic value, and biological functions in breast cancer through integrated bioinformatics and experimental analyses.MethodsTranscriptomic and clinical data from The Cancer Genome Atlas (TCGA) were analyzed to assess CDK1 expression, diagnostic efficacy, and survival associations. Immune infiltration and tumor mutation burden (TMB) were evaluated using TIMER and CIBERSORT algorithms. Single-cell RNA sequencing data from TISCH2 were employed to examine cell-type-specific expression. Functional experiments, including shRNA-mediated CDK1 knockdown, Western blotting, and CCK-8 assays, were performed to validate its biological role in MDA-MB-231 cells.ResultsCDK1 expression was elevated in breast cancer tissues compared with normal controls and exhibited high diagnostic accuracy (AUC = 0.978). Elevated CDK1 levels were associated with HER2-, ER-, and PR-negative subtypes and enriched in Basal-like breast cancer. Patients with high CDK1 expression showed poorer disease-specific survival (HR = 1.67, p = 0.024). Immune analysis revealed positive correlations between CDK1 and immune cell infiltration, particularly CD4+ memory T cells, CD8+ T cells, etc. as well as a moderate association with TMB. Single-cell analysis indicated that CDK1 was preferentially expressed in CD8+ T cells and M1 macrophages. Mechanistically, CDK1 knockdown reduced AKT phosphorylation and downregulated Cyclin D1, A, and E1, leading to suppressed proliferation of breast cancer cells.ConclusionCDK1 acts as a multifaceted oncogenic factor in breast cancer, contributing to tumor growth and immune modulation. Its overexpression is linked to poor prognosis and enhanced immune infiltration, underscoring its potential as a diagnostic and therapeutic target. Targeting CDK1 or its downstream signaling pathways may offer novel strategies, particularly for aggressive subtypes such as Basal-like or triple-negative breast cancer.